Penerapan Morning Actvity untuk Meningkatkan Karakter Mandiri dan Tanggung Jawab - Lestari, Sulastri Puji; Kurnia, Dadang; Hanifah, Nurdinah (Jurnal Pena Ilmiah, 2019)
Education currently focusesion balancing affective domainiwhich is strived through the inculcation of characterieducation that integratediinto subjects, but at Green School SumedangiInternational Elementary School (IGS) it is integrated intoistudent's activities, including morning activity. Morningiactivity is one of habituation programs to evoke a pleasantilearning atmosphere, to train students to beiactive and have positive character. This studyiaims to improve the 3rdigrade students’ independentiand responsible character through theiimplementation of morning activity. The method used is a caseistudy, with 15 students as subjects. The instrumentsiused were questionnaire, interview guidelines, observationiguidelines, study documentation, and fieldinotes. The results showed morningiactivity at IGS has improved the 3rd gradeistudents’ independent and responsibleicharacter, through internalizingiexemplary, planned programs, andisupporting physical and socialilearning environments. School control also carriediout consistently to maintain the qualityiof program, educators and students.